Exergy analysis of energy‐intensive production processes: advancing towards a sustainable chemical industry. Issue 9 (27th May 2014) - Luis, Patricia; Van der Bruggen, Bart
Abstract Exergy analysis is becoming a very powerful strategy to evaluate the real efficiency of a process. Its application in the chemical industry is still at an early stage but many interesting remarks can be obtained from the recent research in the most energy intensive processes of the chemical industry: the production of chemicals, the cement industry, the paper industry and, the iron and steel industry. The present review analyzes the opportunities and challenges in those sectors by considering exergy analyses as the first required step (although not sufficient) to advance towards a more sustainable chemical industry. Social, environmental and economic factors play a role in the critical evaluation of a process and exergy could be considered as the property that joins together those three cores of sustainability. © 2014 Society of Chemical Industry